PENGARUH TATA RUANG DAN LINGKUNGAN KERJA PADA EFEKTIVITAS KERJA DI DINAS SDABMBK KOTA MEDAN - Siregar, Nabila Annisa Rahmadhani; Qarni, Waizul; Daulay, Aqwa Naser (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.02.TAHUN.2025DO - 10.24843/EEB.2025.v14.i02.p08, 2025)
This research contributes to the field of study by enriching the understanding of the influence of office layout and work environment on employee work effectiveness. In addition, this study also develops theories regarding the relationship between spatial design and employee psychological factors such as motivation, stress, and job satisfaction. This research can be extended by comparing the results in the SDABMBK Office with other agencies, both government and private, to obtain a more comprehensive picture. Providing adequate technological tools will improve work efficiency and allow employees to collaborate more easily. In terms of management, implementing more flexible management practices, such as customisable working hours or remote working options, can improve work-life balance and reduce stress levels. This will improve job satisfaction and encourage employees to work more optimally. The practical contribution can also provide guidelines for more adaptive workspace design, taking into account ergonomic factors and collaborative needs in the era of technology and remote work. Further research could explore the long-term impact on productivity, employee retention and job satisfaction, and develop design models that can be applied across different types of organizations, to sustainably improve employee performance.